Caracterização citogenética e molecular de acessos de maracujá da caatinga (Passiflora cincinnata mast.) - Almeida, Larissa Emanuelle da Silva (2018)
Passiflora cincinnata Mast. is a native species of Brazil with a wide geographic distribution, which can be exploited as a source of resistance to biotic and abiotic stresses, presenting good productivity, as well as high nutritional quality for human consumption, besides other uses. On the other hand, both molecular and cytogenetic characterization is an important step for the conservation and use of genotypes, considering the potential genetic diversity of the species. The objective of this work was to characterize the genetic diversity among the passion fruit of the caatinga (P. cincinnata), conserved in the active bank of passion fruit germplasm of Embrapa Semiárido, using cytogenetic techniques of conventional analysis, double CMA3/DAPI staining and using molecular markers from type ISSR. The different ISSR molecular markers showed efficiency in detecting polymorphism, revealing intraspecific variability among the accessions. Diploid chromosome numbers 2n=18 were observed, being classified in the chromosomal group with basic number x=9. The double CMA/DAPI staining allowed the identification of four CMA positive bands, semi-reticulated interphase nuclei with presence of CMA+ blocks. The colorability of the pollen grains using acetic carmine and Alexander reactive allowed to estimate high pollen viability with values above 98% for both dyes analyzed, indicating the potential use of this species in breeding programs.